Peningkatan Kompetensi Pemrograman Siswa Melalui Pelatihan Python Di SMK Panti Karya 3 - Achmad Lutfi Fuadi; Nardiono; Saprudin (AMMA : Jurnal Pengabdian Masyarakat, 2026)
Mastery of computer programming has become an urgent need in the era of the industrial revolution 4.0, especially for Vocational High School (SMK) students who are prepared to enter the workforce directly. However, SMK Panji Karya 3 still faces obstacles in improving students' programming competencies, particularly in Python, due to limited teaching materials and practical training. This community service activity aims to improve students' programming competencies through structured Python training. The methods used include interactive lectures, hands-on practice, and mentoring on small projects. The results of the activity show a significant increase in the understanding of basic programming concepts (such as variables, branching, looping, and functions) and the ability to solve simple case studies. Furthermore, students' enthusiasm and independence in writing code have increased significantly. This training makes a real contribution to preparing SMK Panji Karya 3 students to face the challenges of industry and the workforce.